The 15 g D-xylose absorption test: its application to the study of coeliac disease. Issue 1 (January 1977) - Stevens, F M; Watt, D W; Bourke, M A; McNicholl, B; Fottrell, P F; McCarthy, C F
Abstract : The absorption of xylose following an oral load of 15 g D-xylose has been studied by serial blood levels in 17 untreated adult coeliac patients, 21 treated coeliac patients, and 30 non-coeliac patients. A statistically significant difference in xylose blood levels was found between untreated coeliac and non-coeliac patients at all the times studied, but a complete separation between these two groups occurred only at the 75 minute stage. The reproducibility of absorption was assessed by repeating the test in 16 subjects. The 95% confidence limits of the standard error of estimate are narrowest at 75 and 90 minutes.